2021
DOI: 10.1111/josh.13057
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition‐Exercise Behaviors, Health Literacy Level, and Related Factors in Adolescents in Turkey

Abstract: BACKGROUND Health behaviors of adolescents affect their health and well‐being into adulthood. This study was conducted to determine the nutrition‐exercise behaviors, health literacy level, and related factors in adolescents. METHODS A cross‐sectional design was used for this study. Overall, 810 students in grades 6–8 in a Turkish school completed the study. A personal information form, the Nutrition‐Exercise Behaviors Scale, and the Health Literacy for School‐Aged Children Scale were used for data collection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Inadequate NL and HL are associated with high rates of obesity (15,16). The studies investigating NL in Türkiye a line with our results and suggest that women's NL scores are significantly higher than men's and there is a significant relationship between NL levels and gender and BMI values (14,15,26). In the study of Özdenk and Özcebe (27), contrary to our study, approximately one-third of the participants (32.1%) were found to have adequate NL levels.…”
Section: Studies On Nl and Hl Have Only Recently Begun Insupporting
confidence: 88%
See 1 more Smart Citation
“…Inadequate NL and HL are associated with high rates of obesity (15,16). The studies investigating NL in Türkiye a line with our results and suggest that women's NL scores are significantly higher than men's and there is a significant relationship between NL levels and gender and BMI values (14,15,26). In the study of Özdenk and Özcebe (27), contrary to our study, approximately one-third of the participants (32.1%) were found to have adequate NL levels.…”
Section: Studies On Nl and Hl Have Only Recently Begun Insupporting
confidence: 88%
“…In addition, they have been used in research on evaluating the nutritional status of adults and individuals with chronic diseases (10)(11)(12). In Türkiye, most studies on NL include adolescents, and the number of those evaluating NL and HL in adults is quite limited (13,14). Moreover, no study analyzes the relationship between NL and HL in the same population.…”
Section: Studies On Nl and Hl Have Only Recently Begun Inmentioning
confidence: 99%
“…A recent study by Ayaz-Alkaya & Kulakci-Altintas (2021) confirmed a positive correlation between HL and health nutrition-exercise behavior and meal pattern in students of grades 6-8 in Turkish school [42]. Another study performed among adolescents from Turkey confirmed the association between HL and subdimensions of health lifestyle behaviors, including nutrition [14].…”
Section: Discussionmentioning
confidence: 86%
“… 3 Studies show that more than half of children have only a moderate level of health literacy and this needs to be improved. 5 , 6 , 7 , 8 The development of health literacy in children depends on the health literacy level of their teachers, who spend a lot of time with them in the school environment and are also their role models. 2 , 9 , 10 It is thought that teachers directly influence students' health literacy and can shape these levels.…”
Section: Introductionmentioning
confidence: 99%